Pendidikan Moderasi Beragama sebagai Perisai Radikalisme di Lembaga Pendidikan (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
The phenomenon of religion-based radicalism remains a serious threat to the sustainability of national and state life, including within educational institutions. Educational institutions hold a strategic role in instilling religious values that are peaceful, tolerant, and civilized. Therefore, religious moderation education has become a vital approach as a preventive measure against radical ideologies. This study aims to examine the role and urgency of religious moderation education as a shield against radicalism in educational institutions. The research method employed is a literature study, analyzing various literatures such as books, scientific articles, and policy documents related to religious moderation and character education. The results show that religious moderation education can instill the values of tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and i‘tidal (justice) in students. These values contribute significantly to forming religious attitudes that are inclusive, humanistic, and non-violent. The implementation of religious moderation education in educational institutions can be achieved through curriculum integration, educator role-modeling, the cultivation of school culture, and the strengthening of contextual religious literacy. Thus, religious moderation education plays a crucial role as an ideological and moral fortress in preventing the entry and growth of radicalism within the educational environment.